Understanding climate and land surface changes impact on water resources using Budyko framework and remote sensing data in Ethiopia - Abera, Wuletawu; Tamene, Lulseged D.; Abegaz, Assefa; Solomon, Dawit (Elsevier, 2019)
Climate change and land degradation are the two drivers playing a significant role in changing freshwater availability. Targeted intervention requires understanding the role of each driver and their spatial dominance. However, detangling the effects of these factors and identifying where each plays the most important role is still unclear. In this study, we used Budyko-like framework and remote sensing data to evaluate the spatial effects of climate and land surface changes on water availability in Ethiopia. At national level, the mean long-term annual runoff change after 20 years is positive (about 80 mm/year), and is equally accountable to climate change (50%) and landscape surface changes (50%). However, both the change and contribution of the two factors vary spatially. In northern (Tigray region) and southeastern (Somali region) Ethiopia, the contribution of climate change is larger than the land surface changes on water resources. Particularly in the southeastern part of the country (Somali region), 70% of the changes in water resources is attributed to climate change. In most areas of the country, the change in water resources due to land surface change is positive. The detail percentage contribution of the two factors on the water resource change for each administrative zone is provided.